Antimicrobial properties of gallium (III)-and iron (III)-loaded polysaccharides affecting the growth of escherichia coli, staphylococcus aureus, and pseudomonas aeruginosa, in vitro - Best, Mark G. (2020)
Antimicrobial resistance (AMR) has become a global concern as many bacterial species have developed resistance to commonly prescribed antibiotics, making them ineffective to treatments. One type of antibiotics, gallium(III) compounds, stands out as possible candidates due to their unique “Trojan horse” mechanism to tackle bacterial growth, by substituting iron(III) in the metabolic cycles of bacteria. In this study, we tested three polysaccharides (carboxymethyl cellulose (CMC), alginate, and pectin) as the binding and delivery agent for gallium on three bacteria (Pseudomonas aeruginosa, Escherichia coli, and Staphylococcus aureus) with a potential bioresponsive delivery mode. Two types of analysis on bacterial growth (minimum inhibitory concentrations (MIC) and minimum bactericidal concentrations (MBC)) were carried out while iron(III)-loaded polysaccharide samples were also tested for comparison. The results suggested that gallium showed an improved inhibitory activity on bacterial growth, in particular gallium(III)-loaded carboxymethyl cellulose (Ga-CMC) sample showing an inhibiting effect on growth for all three tested bacteria. At the MIC for all three bacteria, Ga-CMC showed no cytotoxicity effect on human dermal neonatal fibroblasts (HDNF). Therefore, these bioresponsive gallium(III) polysaccharide compounds show significant potential to be developed as the next-generation antibacterial agents with controlled release capability.